GENEOLOGI KEBIJAKAN DESENTRALISASI DARI KOLONIALISTIK HINGGA PASCAKOLONIALISTIK DEMOKRATIK DI INDONESIA - Mursyidin Mursyidin (Universitas Teuku Umar, 2018)
Decentralization has become one of the important phenomena that must be mentioned in the era of the last 10 years, where the great power of the central government in the past (precisely in the New Order era) has now been replaced with the introduction of regional autonomy, although this work is still being carried out, revised here and there , while we also see the phenomenon of more regional leaders (mayors, regents, or governors) who are suspected of corruption cases in various regions. Inevitably corruption becomes something decentralized too. In this situation, where is the position of the local press? Did he participate in guarding the existing democratization process, or did he also become part of the existing problem? Exactly whether we are talking about the role of the local press as a solution to the problem of corruption, or whether the local press is actually part of the problem of corruption. Keywords: Decentralitation, Media, Local Politic